The Effects of Brainstorming and Predicting as Schema Activation Strategies on the Algerian EFL Students’ Reading Comprehension: An Experimental Study at the Department of English, Blida 2 University, Algeria - Abla Benbellal (International Journal of Social Sciences & Educational Studies, 2020)
This research aims at investigating the effects of schema activation, using brainstorming and predicting, on students’ reading comprehension at the English department, Blida 2 University, Algeria. To this end, an experimental research design was adopted where two data collection instruments were used: a students’ questionnaire to elicit students’ attitudes towards reading in English, their difficulties in reading comprehension and use of brainstorming and predicting as schema activation strategies, and an experiment in which two experimental groups were taught how to activate their schemata prior to reading through brainstorming and predicting strategies. The results of the study demonstrated that an interactive reading approach based on activating students’ schemata through brainstorming and predicting had significant effects on the process of comprehending texts and increased students’ motivation to read.